Brand orientation and financial performance nexus - Kaličanin, Đorđe; Veljković, Saša; Bogetić, Zoran (Industrija, 2015)
The aim of the article was to find nexus between brand orientation and financial performance in companies doing business in Serbia. We surveyed general managers, marketing managers, and brand managers in order to examine their views on the brand orientation dimensions of their companies. We matched the survey results with financial performance of those companies (EBITDA margin) in order to find linkages between these variables. We got expected results in the sense that strong brand orientation and weaker brand barriers lead to better financial performance. Overall brand orientation is significantly positively correlated with EBITDA margin, and brand barriers are significantly negatively correlated with that measure. We analysed the brand orientation and brand barriers between groups of companies classified according to their size, internationalization, origin of company ownership, origin of brand, specific business area of key brands and type of goods sold. Interestingly, there are undoubted differences in brand orientation and brand barriers only between foreign and domestic companies. These differences could be seen as one of the main reasons of differences between their EBITDA margins. Also, we saw some differences in brand orientation in case of companies with international brands in relation to companies with domestic brands, but those differences are fewer and smaller. We did not find any other statistically significant difference. The significance of the paper is in emphasizing that development of brand orientation of domestic companies could lead to improvement of their profitability and competitiveness.